Sulfate-reducing bacteria in anaerobic bioprocesses: basic properties of pure isolates, molecular quantification, and controlling strategies. Issue 1 (1st January 2018) - Liu, Ze-hua; Yin, Hua; Lin, Zhang; Dang, Zhi
ABSTRACT: Anaerobic bioprocesses of wastewater, agricultural waste, or excess sludge are desirable as these provide the prospect of energy recovery via methane gas generated. However, hydrogen sulfide (H2 S) generated from reduction of sulfate by sulfate-reducing bacteria (SRBs) during the process is inhibitory to the methane-producing bacteria (MPBs); meanwhile the SRBs and MPBs also compete for utilization of a key substrate in methanogenesis, volatile fatty acids. Therefore, it is quite important to mitigate the adverse impacts of SRBs on methanogenesis. The main objective of this review is to find potential controlling strategies for SRBs. With this in mind, properties of isolated pure SRBs from different sources were firstly summarized, in which 45 isolated pure SRBs belonging to seven phylogenetic lineages that can grow under versatile environments were included; then the state of the art on molecular quantification of SRBs through quantitative polymerase chain reaction was presented, in which related studies focusing on anaerobic bioprocesses were collated. Finally, potential effective controlling strategies of SRBs were outlined and discussed, which include enhancement/inhibition of H2 S production as well as onsite elimination of H2 S formed.